EDITORIAL - Hayes, Grahame (PINS-Psychology in Society, 2025)
Mostly people marvel at the wonder and benefits of the Internet, and mostly it seems we are right to do so. We also bemoan the problems created by the Internet, which range from right-wing hate forums, to the inane mountains of available information, to the obsessive checking of emails and other social network “postings”, to the ubiquity of the new verb – “just google it”! And yet intellectual life is so imbricated with the Internet that we forget how recent its founding is, and how intellectual communities formed and functioned before the Internet. For much of its nearly 30 year history PINS has functioned as a kind of virtual intellectual community, firstly for people who wanted to be associated with a psychology that was actively anti-apartheid, and secondly for people who want to maintain a constructive social critique of psychological theory and practice in post-apartheid society.